Childhood burns in south eastern Nigeria - Okoro Philemon; Igwe Patrick; Ukachukwu Alvan (Wolters Kluwer Medknow Publications, 2009)
Background: Burns injuries are recognized as a major health problem worldwide. In children and, particularly, in our environment where poverty, ignorance and disease are still high, they constitute significant morbidity and mortality. Previous studies on this topic in parts of Nigeria either lumped adults and children together or were retrospective. We, therefore, prospectively studied the current trends in burns in children. Patients and Methods: This prospective study of burns spanned over a period of 18 months (June 2006-December 2007) at the Paediatric Surgery Units of the Imo State University Teaching Hospital, Orlu, and the Federal Medical Centre, Owerri, Imo State. Data were collected and analysed for age, sex, cause/type of burn, place of burn, presence or absence of adult/s, initial prehospital intervention, interval between injury and presentation, surface area and depth of burn and treatment and outcome. Results: Fifty-three patients were studied, 31 (58.4%) were male and 22 (41.6%) were female (M:F = 1.4:1). Patients mostly affected were aged 2 years and below. The most common cause of burns was hot water in 31 (58.5%) patients. The vast majority of these injuries happened in a domestic environment (92.5%) and in the presence of competent adult/s (88.7%). Outcome of treatment was good: there were two (3.8%) deaths and 46 (86%) patients had complete recovery. Conclusion: Burns is still a major health problem among children in south eastern Nigeria. Fortunately, outcome of appropriate treatment is good. However, we think that poor safety consciousness among parents is a major predisposing factor. Public enlightenment on measures to ensure safe home environment may be necessary to avoid or limit childhood burns.